IFIP International Federation for Information Processing
DOI: 10.1007/978-0-387-75462-8_20
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Non-Discoverable Bluetooth Devices

Abstract: Mobile communication technologies such as Bluetooth are becoming ubiquitous, but they must provide satisfactory levels of security and privacy. Concerns about Bluetooth device security have led the specification of the "non-discoverable" mode, which prevents devices from being listed during a Bluetooth device search process. However, a nondiscoverable Bluetooth device is visible to devices that know its address or can discover its address. This paper discusses the detection of non-discoverable Bluetooth device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In addition to privacy concerns, Bluetooth technology also has some security concerns (Munro, 2008;Wong and Stajano, 2005;Cross et al, 2007). Wong and Stajano (2005) reported that the MAC address in Bluetooth is closely tied into the access procedure of the device.…”
Section: The Security Of a Bluetooth Devicementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to privacy concerns, Bluetooth technology also has some security concerns (Munro, 2008;Wong and Stajano, 2005;Cross et al, 2007). Wong and Stajano (2005) reported that the MAC address in Bluetooth is closely tied into the access procedure of the device.…”
Section: The Security Of a Bluetooth Devicementioning
confidence: 99%
“…Wong and Stajano (2005) reported that the MAC address in Bluetooth is closely tied into the access procedure of the device. Cross et al (2007) showed that even if a Bluetooth device is not in discovery mode, algorithms can be designed to gain access into the device in less than 24 hours.…”
Section: The Security Of a Bluetooth Devicementioning
confidence: 99%
“…The variation of the detection rate indicates that this can be a localisation parameter. In addition, due to security reasons, some Bluetooth devices change to non-discoverable mode if they are not in use [99] for a period of time. Not all Bluetooth devices reply to inquiry packets when they are paired and connected to another Bluetooth device [4].…”
Section: Only Detect a Proportion Of Passing Vehiclesmentioning
confidence: 99%
“…Therefore, the actual number of vehicles is much lower in my collected data, and this small proportion of co-detections do not affect the estimated traffic volume and traffic characteristics. However as explained in Chapter 3, Section 3.3 due to security reasons, some Bluetooth devices change to non-discoverable mode if they are not in use [99] and not all Bluetooth devices reply to inquiry packets when they are paired and connected to another Bluetooth device [4]. Therefore, the chance of multi-tenancy detection can be very low in the collected data as this is the case in the collected data.…”
Section: Outputs Of Mtdibtmentioning
confidence: 99%
“…The variation of the detection rate indicates that this can be a localisation parameter. In addition, due to security reasons, some Bluetooth devices change to non-discoverable mode if they are not in use [99] for a period of time. Not all Bluetooth devices reply to inquiry packets when they are paired and connected to another Bluetooth device [4].…”
Section: Only Detect a Proportion Of Passing Vehiclesmentioning
confidence: 99%